2020
DOI: 10.1002/acr.23882
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Preliminary Outcomes of a Physical Therapist–Administered Physical Activity Intervention After Total Knee Replacement

Abstract: Objective. To explore the feasibility, fidelity, safety, and preliminary outcomes of a physical therapist-administered physical activity (PA) intervention after total knee replacement (TKR).Methods. People who had undergone a unilateral TKR and were receiving outpatient physical therapy (PT) were randomized to a control or intervention group. Both groups received standard PT for TKR. The intervention included being provided with a Fitbit Zip, step goals, and 1 phone call a month for 6 months after discharge fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
106
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(113 citation statements)
references
References 35 publications
1
106
2
Order By: Relevance
“…Physical activity studies were consistent in the number of sensors implemented, with 21 studies (81%) using a single sensor for activity measurements 35–40 42 43 45–57. As technology and availability of wearable accelerometers has progressed, the type of sensor used has also changed.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Physical activity studies were consistent in the number of sensors implemented, with 21 studies (81%) using a single sensor for activity measurements 35–40 42 43 45–57. As technology and availability of wearable accelerometers has progressed, the type of sensor used has also changed.…”
Section: Resultsmentioning
confidence: 85%
“…In studies published between 2008 and 2016, nine studies (69%)36 37 40 42 44 45 58–60 reported using a uniaxial accelerometer versus just three studies (23%)46 55 56 using a triaxial accelerometer. Conversely, in studies published in 2017–2019, eight studies (62%)35 38 47 49 50 53 54 57 reported using a triaxial accelerometer, while only three (23%)39 43 45 used a uniaxial accelerometer. Overall, three studies did not report the number of axes recorded,41 48 51 and most studies within this subgroup (73%)36 37 40–45 47 48 50–55 57 60 did not report the sampling rate at which data were collected.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations